The Imposition of Pretrial Conditions on Released Federal Defendants: The Overuse of Conditions Without Providing Any Measurable Benefits - Cohen, Thomas H. (Criminal justice and behavior, 2023)
In the federal system, defendants placed on pretrial release may have multiple conditions imposed on them which are aimed at ensuring court appearances and maintaining public safety. In general, little is known about the number of conditions imposed on released federal defendants, the extent to which conditions are associated with pretrial risk, and the potential of these conditions to maximize court appearances and minimize pretrial crime. This study seeks to address these issues by examining the imposition of pretrial conditions on 223,260 released federal defendants. The results show that defendants received an average of about nine conditions and that the association between conditions and a defendant’s pretrial risk classification was relatively modest. The results also show conditions having no significant relationship with reductions in the likelihood of pretrial crime or missed court appearances; however, the probability of being revoked increases with the number of conditions imposed.